Starch-based environment friendly, edible and antimicrobial films reinforced with medicinal plants - Ali, Amjad; Basit, Abdul; Hussain, Azhar; Sammi, Shehla; Wali, Asif; Goksen, Gulden; Muhammad, Ali; Faiz, Furukh; Trif, Monica; Rusu, Alexandru; Manzoor, Muhammad Faisal (Frontiers in Nutrition, 2023)
In the current study, cornstarch-based antimicrobial and edible films were designed using solution-casting methods. The medicinal plants (Acontium heterophyllum, Artemisia annua, and Thymus serpyllum) reinforced the gelatinized solution in different concentrations as fillers. The effect of plant extracts on antimicrobial and antioxidant potential, microstructure, barrier, thermal and mechanical properties of cornstarch-based films (SBFs) was investigated using antimicrobial activity, DPPH free radical scavenging values, scanning electron microscopy, X-ray diffraction, water vapor transmission rate, differential scanning calorimetry, and tensile strength. Likewise, it was depicted that the geometric and crystalline structures of medicinal plants’ reinforced films remained the same even after processing. The mechanical tests indicated that the plant extracts effects are associated with reduced elongation, increasing tensile strength, and Young’s modulus. Morphological analysis revealed the generation of uniform and the compact surfaces. However, films with 10% concentration of plant extracts have the lowest water vapor permeability values, and emerged better barrier properties. Moreover, these films showed the significant antioxidant potential and antimicrobial activity.